Larvicidal Activity and Histopathological Midgut Alteration of Aedes Aegypti Larvae Induced by Methanol Extract Mahkota Dewa fruit (Phaleria Macrocarpa (Scheff). Boerl) - Nurul Eliza; Rizal Subahar; Agus Aulung (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Aedes aegypti is the main vector of DHF in Indonesia. The use of synthetic insecticide results in vector resistance. Mahkota Dewa fruits (Phaleria macrocarpa (Scheff) Boerl) contain flavonoids, saponins, and tannins. Thus, it has the potential as a natural larvicide against Ae. aegypti larvae. The objective of the study was to determine the effectiveness of methanol extract Mahkota Dewa fruit. This research was experimental, used methanol extract Mahkota Dewa fruit at concentration 0.1%, 0.15%, 0.20%, 0.25% and 0.30%, then added 25 larvae each concentration and repeated 3 times. After 24 and 48 hours of exposure, the mortality of larva was counted and then calculated LC50 and anterior midgut histopathology. LC50 values 0,554% (0,391-11,397) and anterior midgut histopathology shows epithelial damage. Mahkota Dewa fruits with methanol extract have activity as larvicide larvae instar III-IV Ae. aegypti.